The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/4430594
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cognitive Empathy in Outpatients with Chronic Musculoskeletal Pain: A Cross-Sectional Study

Abstract: Background. In recent years, a growing number of researchers showed significant interest in psychological and social interventions to manage chronic musculoskeletal (MSK) pain. Cognitive and emotional empathy is an attractive and valuable sociopsychological factor that may provide protection and resilience against chronic MSK pain. However, its effect on outpatients remains underexplored. Objective. To compare the empathy ability between chronic MSK pain outpatients and healthy controls and explore the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previous studies have found that many diseases had empathy disorders, such as psychiatric disorders (Decety and Moriguchi, 2007 ; Bragado-Jimenez and Taylor, 2012 ; Schreiter et al, 2013 ) and chronic pain (Sohn et al, 2016 ; De Tommaso et al, 2019 ; Ma et al, 2020 ; Mu et al, 2021 ; Zhang et al, 2021 ). It would be meaningful to see if the extension of MBIs to these subjects could improve their empathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that many diseases had empathy disorders, such as psychiatric disorders (Decety and Moriguchi, 2007 ; Bragado-Jimenez and Taylor, 2012 ; Schreiter et al, 2013 ) and chronic pain (Sohn et al, 2016 ; De Tommaso et al, 2019 ; Ma et al, 2020 ; Mu et al, 2021 ; Zhang et al, 2021 ). It would be meaningful to see if the extension of MBIs to these subjects could improve their empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy also facilitates helping behavior, cooperation, and altruism (Feldmanhall et al, 2015 ). Impaired empathy is manifested by lacking understanding of the pain and plight of others, difficulty to be impressed, and appearing indifferent in real life, which is common in many psychiatric disorders (Decety and Moriguchi, 2007 ; Bragado-Jimenez and Taylor, 2012 ; Schreiter et al, 2013 ) and chronic pain (Sohn et al, 2016 ; De Tommaso et al, 2019 ; Ma et al, 2020 ; Mu et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven theoretically informed models based on increasing complexity were assessed (see Supporting Information: Figure ). First, we examined a one‐factor model (model 1) comprised of a general factor, then a two‐factor model (model 2) generally distinguishing between cognitive and affective components of empathy (Cuff et al, 2016), and a three‐factor model (model 3) that distinguished valences in cognitive empathy (Rueda et al, 2015; Zhang et al, 2021). Second, another three‐factor model (model 4) was constructed that distinguished between negative and positive valences in affective empathy (Löchner et al, 2022; Yan et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Perspective-taking and reading facial expressions are both cognitive evaluative aspects of empathy [5]. The term "emotional empathy" is used to describe the vicarious sharing of emotion; the emotional components engage a partial affective sharing of others' affective states [6]. For instance, individuals vicariously experience the unpleasantness associated with the pain someone else is feeling.…”
Section: Introductionmentioning
confidence: 99%